Why local people prefer to buy imported shoes rather than local shoes / Norazwafira Mat Nor and Noorshida Kamarullbahrin - Mat Nor, Norazwafira; Kamarullbahrin, Noorshida (Faculty of Business and Management, 2001)
This proposal is to indicate whether most local people choose to buy imported shoes than local shoes. Our purpose of this proposal is to know why local people prefer to buy imported shoes. Besides, we want to know what are the factors that influence local people to buy imported shoes. We also want to know what are the problems that might be faced when most local people use imported shoes.